RETRACTED: Analisis Pengaruh Indeks Pembangunan Manusia Terhadap Jumlah Penduduk Miskin Pada Provinsi Banten - Dyah Ayu Dwi Pitaloka; Kharisma Zahro Awalluna; Deris Desmawan (Universitas Teuku Umar, 2023)
This study is an analysis of data from BPS Banten sources with the aim of identifying the impact of the Human Development Index on poverty rates in Banten during the period 2012-2021 in order to examine the phenomenon of poverty in Banten. It is determined by applying a simple linear regression method by a supporting software application, namely SPSS or Statistical Product and Service Solutions one variable method and produces an output that T count 1.953 < t table 2.3060 and sig 0.087 < 0.05 which means that there is no significant effect between Human Development Index and Number of Poor Population. It was concluded that the Human Development Index is one of the indicators or variables that affect the Number of Poor Population in Banten province, but not too significant. This is because there are still many variables that can affect the size of the population It is poor in Banten province so that one variable does not really affect the dependent variable. Therefore, it is hoped that the local government will still get basic services such as education and health which are expected to be developed evenly in areas that are relatively low-income. living, especially in rural areas, as well as improving the quality of the population.